An aid to electrocardiogram - Sarker, Harendra Nath (New Delhi : Japee Brothers Medical Publishers, 2014)
.Concise guide to ECG for trainees covering elementary knowledge, ECG interpretation, arrhythmia, systemic ECG and pericarditis (inflammation of the pericardium, the sac that surrounds the heart). Helps with pattern recognition, points out key salient features and helps trainees understand the logic behind ECG manifestations.
Guía concisa de ECG para aprendices que cubre conocimientos elementales, interpretación de ECG, arritmia, ECG sistémico y pericarditis (inflamación del pericardio, el saco que rodea el corazón). Ayuda con el reconocimiento de patrones, señala las características más destacadas y ayuda a los alumnos a comprender la lógica detrás de las manifestaciones del ECG.
Contents PART ONE Section 1. Elementary knowledge Section 2. ECG interpretation Section 3. Arrhythmia Section 4. Myocardial infarction PART TWO Section 5. Systemic ECG Section 6. Pericarditis
Keywords: ELECTROCARDIOGRAPHY; ELECTROCARDIOGRAFÍA; ECTROCARDIOGRAMA; ARRITMIA